Examining the School Climate and Teachers' Commitment to the Teaching Profession: Basis for a Supplementary Support Program - Jacinto, Rosalie Q. (Future Science / FSH-PH Publications, 2022)
This research is intended to examine the extent of effectiveness of school climate and level of teachers’ commitment to the teaching profession. To attain this purpose, the researcher utilized descriptive-correlational research design to investigate the relationship between school climate and teachers’ commitment. The researcher composed a survey questionnaire which was subjected to validity and reliability tests and was administered to a convenient sample of a public junior high school teachers in the locale of the study. Findings reveal that the extent of effectiveness of school climate dimensions was highly effective, and teachers’ level of commitment was highly employed. The result served as the bases for the researcher to propose a supplementary support program to improve further the school climate and strengthen the level of teachers’ commitment, hence improving their schoolwork performance.